Traumatic deep neck infection due to pulling a tooth with pliers - Avcı, Sema (Acta Biomedica Atenei Parmensis, 2018)
Deep neck infection is life-threatening and mortal condition that requires immediate treatment. This infection is generally polymicrobial and frequently seen after upper respiratory infections, poor dental hygiene, trauma and surgery to the head and neck region. The symptoms of deep neck infections are swelling, dysphagia, pain, trismus, dysphonia and otalgia. Deep neck infections can be seen at any age and its mortality is about 20-50%. Initial management of the deep neck infection is intravenous antibiotic, protection of airway and drainage of abscess. Deep neck infections can cause severe complications even dead can be seen, so physicians should be aware of these complication. Herein, we reported a 71-year-old-woman suffering from traumatic deep neck infection due to pulling a tooth with pliers.